DEVELOPMENT PATTERN OF KAMPUNG AGRO INNOVATION SYSTEM IN BANJAR CITY - Perdi Setiawan; Iwan Setiawan; Hepi Hapsari (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The agribusiness sector which collaborates with the tourism sector is one of the solutions in the improvement effort of Indonesia's economy. There are various ways to unite the agribusiness and tourism sectors, one of which is the development of tourism villages. Kampung Agro is a tourist village in Banjar City that allows visitors to learn to choose and pick their ready-to-harvest honey star fruit which then can be consumed directly. However, various problems still hinder the development of Kampung Agro. The management of Agro Village still relies on traditional methods without involving any innovation or technology, mainly due to the lack of coordination with farmers and minimal involvement of various stakeholders. The development of Agro Village should be carried out through a collective effort involving various stakeholders who are involved in it. This study aims to construct the development pattern of the Kampung Agro innovation system in Banjar City. The research method used is a case study with a qualitative approach data obtained from primary and secondary sources. This study used the Soft System Methodology (SSM) analytical tool approach. The results showed that in the development of Kampung Agro it is necessary to apply a pattern that involves various parties, including managers, Banjar City Government, academics, business actors and the media to make various efforts through their duties and functions. The parties involved need to collaborate in the management of Agro Village through collective efforts by implementing various actions in accordance with recommended improvement measures. There is a need for support and involvement from the Banjar City Government, in the form of education, assistance policies, as well as mentoring and supervision.